Polarizer with phase difference layer and image display device with polarizer with phase difference layer
Patent Information
- Application Number
- JP2023126537
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0006】 本発明の実施形態によれば、干渉ムラおよび打痕の発生が抑制された位相差層付偏光板を提供し得る。
Smart Images

Figure 2025022190000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with a retardation layer and an image display device having the polarizing plate with a retardation layer. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming popular. In these image display devices, a polarizing plate with a retardation layer is used for the purpose of improving display characteristics and preventing reflection. The polarizing plate with a retardation layer can usually be laminated on an image display panel via an adhesive layer. A substrate, wiring, etc. are arranged on the surface of the image display panel. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-14611 Summary of the Invention [Problem to be solved by the invention]
[0004] When a polarizing plate with a retardation layer is bonded to an image display panel, dents may occur on the viewing side (i.e., the side not in contact with the image display panel) of the polarizing plate with a retardation layer. The retardation layer, which is an alignment and solidification layer of a liquid crystal compound, is thinner than a retardation layer made of a resin film, so that dents tend to occur easily. In addition, when two or more retardation layers, which are liquid crystal alignment and solidification layers, are laminated, interference unevenness may become a problem. In order to suppress interference unevenness, it is known to dispose a pressure-sensitive adhesive layer between the retardation layers. However, when a pressure-sensitive adhesive layer is disposed, dents may become more noticeable. The main object of the present invention is to provide a polarizing plate with a retardation layer that achieves both suppression of interference unevenness and suppression of dents. [Means for solving the problem]
[0005] 1. A polarizing plate with a retardation layer according to an embodiment of the present invention includes, in this order, a polarizing plate including a polarizer; a first retardation layer which is a layer with a solidified alignment of a liquid crystal compound; a resin film; and a second retardation layer which is a layer with a solidified alignment of a liquid crystal. A slow axis of the first retardation layer intersects with a slow axis of the second retardation layer and also intersects with an absorption axis of the polarizer. The resin film has a thickness of 10 μm to 30 μm. 2. In the retardation layer-attached polarizing plate according to the above item 1, the resin film is laminated to the first retardation layer via a first adhesive layer, and the average refractive index n AD1 and the average refractive index n of the resin film RF may satisfy the following relationship: -0.03 <n AD1 -n RF <0.05 3. In the retardation layer-attached polarizing plate according to the above 1 or 2, the resin film is laminated to the second retardation layer via a second adhesive layer, and the average refractive index n AD2 and the average refractive index n of the resin film RF may satisfy the following relationship: -0.03 <n AD2 -n RF <0.05 4. In the polarizing plate with a retardation layer described in any one of 1 to 3 above, the resin film is laminated to the first retardation layer via a first adhesive layer, and the resin film is laminated to the second retardation layer via a second adhesive layer, and the total thickness of the first adhesive layer, the resin film, and the second adhesive layer may be 12 μm to 40 μm. 5. In the retardation layer-attached polarizing plate according to any one of the above items 1 to 4, the resin film may be a cyclic olefin resin film or a cellulose resin film. 6. In the retardation layer-attached polarizing plate according to any one of the above items 1 to 5, the resin film may have a refractive index distribution of nx=ny>nz. 7. In the polarizing plate with a retardation layer according to any one of 1 to 6 above, the first retardation layer may have Re(550) of 200 nm to 300 nm, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer may be 10° to 20°, and the second retardation layer may have Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer may be 70° to 80°. 8. In the retardation layer-attached polarizing plate according to any one of the above 2 to 7, the adhesive layer may be an adhesive layer. 9. In another aspect of the embodiment of the present invention, there is provided an image display device, which comprises the retardation layer-attached polarizing plate according to any one of 1 to 8 above. 10. The image display device according to 9 above may be an organic electroluminescence display device. Effect of the Invention
[0006] According to the embodiment of the present invention, it is possible to provide a retardation layer-attached polarizing plate in which the occurrence of interference unevenness and dents is suppressed. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0010] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 of the illustrated example includes a polarizing plate 10 including a polarizer 11; a first retardation layer 31 which is an alignment solidified layer of a liquid crystal compound (hereinafter, also referred to as a liquid crystal alignment solidified layer); a resin film 50; and a second retardation layer 32 which is a liquid crystal alignment solidified layer, in this order. The polarizing plate 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. The protective layer 13 may be omitted. For example, when the retardation layer can also function as a protective layer, the protective layer 13 may be omitted. In the retardation layer-attached polarizing plate 100, the slow axis of the first retardation layer 31 and the slow axis of the second retardation layer 32 cross each other, and the slow axis of the first retardation layer 31 and the absorption axis of the polarizer 11 cross each other. For example, as described later, the angle between the slow axis of the first retardation layer 31 and the absorption axis of the polarizer 11 may be 10° to 20°, and the angle between the slow axis of the second retardation layer 32 and the absorption axis of the polarizer 11 may be 70° to 80°. The resin film 50 is preferably laminated to the first retardation layer 31 via a first adhesive layer 41, and laminated to the second retardation layer 32 via a second adhesive layer 42. In this specification, the adhesive layer refers to an adhesive layer or a pressure-sensitive adhesive layer. In the illustrated example, the resin film 50 is laminated to the first retardation layer 31 via the first adhesive layer 41, which is a pressure-sensitive adhesive layer, and laminated to the second retardation layer 32 via the second adhesive layer 42, which is a pressure-sensitive adhesive layer. FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. In this illustrated example, the resin film 50 is laminated to the first retardation layer 31 via the first adhesive layer 22, which is preferably an adhesive layer, and to the second retardation layer 32 via the second adhesive layer 23, which is an adhesive layer. The thickness of the resin film 50 is 10 μm to 30 μm. The retardation layer, which is a liquid crystal alignment solidified layer, is thin and can contribute to making the retardation layer-attached polarizing plate thinner. On the other hand, a problem of the occurrence of dents when bonding to a liquid crystal panel may occur. In addition, in a retardation layer-attached polarizing plate including a plurality of retardation layers, which are liquid crystal alignment solidified layers, the retardation layers may cause thin film interference, resulting in interference unevenness. As a method for eliminating interference unevenness, for example, a pressure-sensitive adhesive layer is known to be disposed between the retardation layers, which are liquid crystal alignment solidified layers.However, when a pressure-sensitive adhesive layer is disposed, the occurrence of dents during lamination to a liquid crystal panel may become more pronounced. Therefore, it may be difficult to simultaneously suppress the occurrence of dents and suppress interference unevenness. As described above, in the polarizing plate with a retardation layer according to the embodiment of the present invention, a resin film having a thickness of 10 μm to 30 μm is disposed between the retardation layers, which are liquid crystal alignment solidified layers. With such a polarizing plate with a retardation layer, it is possible to provide a polarizing plate with a retardation layer that can simultaneously suppress the occurrence of dents and suppress interference unevenness, which have been difficult to achieve so far.
[0011] As described above, the resin film is laminated to the first retardation layer, preferably via a first adhesive layer. In this embodiment, the average refractive index n AD1 and the average refractive index of the resin film, n RF It is preferable that the average refractive index n of the first adhesive layer satisfies the following relationship: AD1 and the average refractive index n RF If the following relationship is satisfied, interference unevenness can be further suppressed. The refractive index can be measured by an Abbe refractometer or a prism coupler under the conditions of 25°C and 589 nm. The refractive index of the adhesive layer was measured using a laminate (polymer film / adhesive layer / polymer film) in which the adhesive used to form the adhesive layer was applied to any suitable polymer film (e.g., cycloolefin resin film) to form an adhesive layer (thickness 100 μm), and then the polymer film was laminated on the adhesive layer. In this specification, the average refractive index refers to the average value of nx, ny, and nz. -0.03 <n AD1 -n RF <0.05
[0012] As described above, the resin film is laminated to the second retardation layer, preferably via the second adhesive layer. In this embodiment, the average refractive index n AD2 and the average refractive index of the resin film, n RF It is preferable that the average refractive index n of the second adhesive layer satisfies the following relationship: AD2 and the average refractive index n RF If and satisfy the following relationship, interference unevenness can be further suppressed. -0.03 <n AD2 -n RF <0.05
[0013] In one embodiment, the resin film is preferably laminated to the first retardation layer via a first adhesive layer, and is laminated to the second retardation layer via a second adhesive layer. In this embodiment, the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is preferably 12 μm to 40 μm, more preferably 12 μm to 35 μm, and even more preferably 15 μm to 30 μm. If the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is within the above range, interference unevenness can be further suppressed. Furthermore, when the obtained retardation layer-attached polarizing plate is used in an image display device, a very excellent reflection hue can be achieved.
[0014] The retardation layer-attached polarizing plate may further include another retardation layer in addition to the first retardation layer and the second retardation layer. The other retardation layer may be typically provided on the outside of the second retardation layer 32 (the side opposite to the polarizer 10). The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, and the like of the other retardation layer may be appropriately set according to the purpose. The refractive index properties of the other retardation layer typically have the relationship nz>nx=ny.
[0015] The retardation layer-attached polarizing plate 100 may have an adhesive layer 60 as the outermost layer. The retardation layer-attached polarizing plate 100 can be attached to an image display device (substantially, an image display panel) via the adhesive layer 60. For practical purposes, it is preferable that a release liner is temporarily attached to the surface of the adhesive layer 60 until the retardation layer-attached polarizing plate is used. By temporarily attaching the release liner, the adhesive layer is protected until actual use, and the retardation layer-attached polarizing plate can be rolled.
[0016] The thickness of the retardation layer-attached polarizing plate may be set to any appropriate value. In one embodiment, the total thickness of the retardation layer-attached polarizing plate is preferably 150 μm or less, more preferably 140 μm or less, even more preferably 120 μm or less, more preferably 100 μm or less, even more preferably 90 μm or less, and particularly preferably 85 μm or less. The total thickness of the retardation layer-attached polarizing plate may be, for example, 30 μm or more. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of the polarizing plate, the retardation layer, the resin film, and the adhesive layer for laminating them (that is, the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the outermost pressure-sensitive adhesive layer and the thickness of the release liner that may be temporarily attached to the surface of the outermost pressure-sensitive adhesive layer).
[0017] The components of the retardation layer-attached polarizing plate will be described in more detail below.
[0018] B. Polarizing plate B-1.Polarizer A polarizer is typically composed of a resin film containing a dichroic material (typically, iodine). As the resin film, any appropriate resin film that can be used as a polarizer can be adopted. The resin film is typically a polyvinyl alcohol resin (hereinafter, referred to as "PVA resin") film. The resin film may be a single-layer resin film or a laminate of two or more layers.
[0019] A specific example of a polarizer composed of a single-layer resin film is a PVA-based resin film that has been subjected to a dyeing treatment with iodine and a stretching treatment (typically, uniaxial stretching). The dyeing with iodine is performed, for example, by immersing the PVA-based resin film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be performed after the dyeing treatment or while dyeing. Alternatively, the film may be dyed after stretching. If necessary, the PVA-based resin film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based resin film in water and washing it before dyeing, not only can dirt and antiblocking agents on the surface of the PVA-based resin film be washed off, but also uneven dyeing can be prevented by swelling the PVA-based resin film.
[0020] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA in advance, problems such as a decrease in the orientation or dissolution of the PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the polyvinyl alcohol molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained through a treatment process in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by the drying shrinkage treatment.The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP-A-2012-73580 (Patent No. 5414738) and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.
[0021] The thickness of the polarizer is preferably 1 μm to 30 μm, more preferably 1 μm to 25 μm, further preferably 1 μm to 15 μm, further more preferably 1 μm to 10 μm, and particularly preferably 1 μm to 8 μm. When the thickness of the polarizer is within the above range, the retardation layer-attached polarizing plate can be made thinner.
[0022] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The degree of polarization P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The degree of polarization is typically calculated by the following formula based on the parallel transmittance Tp and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0023] B-2.Protective layer The protective layers 12 and 13 are formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the films include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0024] The polarizing plate with a retardation layer is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.
[0025] The thickness of the protective layer is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm. When a surface treatment is applied, the thickness of the outer protective layer (protective layer 12) includes the thickness of the surface treatment layer.
[0026] C. Retardation layer As described above, the first retardation layer and the second retardation layer are liquid crystal alignment solidified layers. When the retardation layer is a liquid crystal alignment solidified layer, the dents may become more noticeable when the retardation layer is attached to the image display panel. In addition, interference unevenness may occur due to thin film interference of the liquid crystal alignment solidified layer. As described above, in the embodiment of the present invention, the first retardation layer is a liquid crystal alignment solidified layer, a resin film having a thickness of 10 μm to 30 μm, and a second retardation layer is a liquid crystal alignment solidified layer, in this order. If a resin film having a thickness of 10 μm to 30 μm is laminated between the retardation layers being liquid crystal alignment solidified layers, it is possible to suppress both interference unevenness and dents. The retardation layer may further include an alignment film and / or a substrate. As described above, the slow axis of the first retardation layer and the absorption axis of the polarizer intersect, and the slow axis of the first retardation layer and the slow axis of the second retardation layer intersect. The angle between the slow axis of the first retardation layer and the absorption axis of the polarizer, and the angle between the slow axis of the first retardation layer and the slow axis of the second retardation layer can be set to any appropriate value depending on the design. In this section, the first retardation layer and the second retardation layer are collectively described as the retardation layer. When it is necessary to distinguish between the first retardation layer and the second retardation layer, "first" and "second" are clearly indicated.
[0027] The first retardation layer preferably has Re(550) of 200 nm to 300 nm, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°. The second retardation layer preferably has Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°. In this embodiment, either the first retardation layer or the second retardation layer may function as a λ / 4 plate, and the other may function as a λ / 2 plate. For example, when the first retardation layer functions as a λ / 2 plate and the second retardation layer functions as a λ / 4 plate, the Re(550) of the first retardation layer is preferably 200 nm to 300 nm, more preferably 200 nm to 270 nm, further preferably 210 nm to 260 nm, and particularly preferably 230 nm to 260 nm. The Re(550) of the second retardation layer is preferably from 100 nm to 200 nm, more preferably from 100 nm to 170 nm, further preferably from 110 nm to 150 nm, and particularly preferably from 110 nm to 130 nm.
[0028] The thickness of the first retardation layer can be adjusted, for example, to obtain a desired in-plane retardation of the λ / 2 plate. The thickness of the first retardation layer is, for example, 2.0 μm to 4.0 μm. The thickness of the second retardation layer can be adjusted, for example, to obtain a desired in-plane retardation of the λ / 4 plate. The thickness of the second retardation layer is, for example, 0.5 μm to 2.5 μm.
[0029] In this embodiment, the angle formed between the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°. Also, the angle formed between the slow axis of the second retardation layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. In this embodiment, the first retardation layer and the second retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light.
[0030] In the first retardation layer and the second retardation layer, at least one of them typically exhibits a refractive index characteristic showing a relationship of nx > ny = nz. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3.
[0031] In this embodiment, examples of the liquid crystal compound used for the first retardation layer and the second retardation layer include a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The mechanism for expressing the liquid crystallinity of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.
[0032] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0033] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and further preferably 60°C to 90°C.
[0034] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. As the liquid crystal monomer, a nematic liquid crystal monomer is preferable. Specific examples of the liquid crystal compound and the details of the method for forming the alignment solidification layer are as described above.
[0035] Although the first retardation layer functions as a λ / 2 plate and the second retardation layer functions as a λ / 4 plate, the first retardation layer may be a λ / 4 plate and the second retardation layer may be a λ / 2 plate. In addition, the angle between the axis angle of the first retardation layer and the absorption axis of the polarizer is 10° to 20° (about 15°) and the angle between the axis angle of the second retardation layer and the absorption axis of the polarizer is 60° to 80° (about 75°) in the above description, but the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer may be about 75°, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer may be about 15°.
[0036] D. Resin film Any suitable resin film can be used as the resin film. As described above, if the resin film is laminated between the first retardation layer and the second retardation layer via the first adhesive layer and the second adhesive layer, a retardation layer-attached polarizing plate in which the occurrence of interference unevenness and dents is suppressed can be provided. Any suitable resin can be used as the resin constituting the resin film. For example, cyclic olefin resins such as norbornene resin, cellulose resins such as triacetyl cellulose resin, acrylic resins, polycarbonate resins, etc. are listed. Cyclic olefin resins and cellulose resins are preferred. Only one type of resin may be used, or two or more types may be used in combination. In addition, the resin film may be a single film or a laminate of two or more. It is preferable that the resin film is not stretched (unstretched resin film).
[0037] The thickness of the resin film is 10 μm to 30 μm, preferably 10 μm to 25 μm, and more preferably 12 μm to 20 μm. If the thickness of the resin film is within the above range, the occurrence of interference unevenness and dents can be suppressed. As described above, in one embodiment, the thickness of the resin film can be adjusted so that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 10 μm to 30 μm.
[0038] The resin film may have any suitable refractive index distribution. In one embodiment, the resin film may be a so-called negative C plate, which preferably satisfies the refractive index distribution of nx=ny>nz. If the resin film is a negative C plate, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided.
[0039] Average refractive index of resin film n RF can be set to any suitable value. For example, the average refractive index n AD1 and the average refractive index n RF and / or the average refractive index n of the second adhesive layer AD2 and the average refractive index n RF The difference between the average refractive index of the resin film and the average refractive index n RF is preferably 1.40 to 1.60, more preferably 1.45 to 1.55, and further preferably 1.47 to 1.53. When the resin film has an average refractive index within the above range, a retardation layer-attached polarizing plate in which interference unevenness is further suppressed can be obtained.
[0040] The smaller the in-plane retardation Re(550) of the resin film, the more preferable. The in-plane retardation Re(550) of the resin film is preferably 20 nm or less, more preferably 15 nm or less, even more preferably 10 nm or less, and particularly preferably 5 nm or less. If the in-plane retardation Re(550) of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided. The in-plane retardation Re(550) is, for example, 0 nm or more.
[0041] The smaller the absolute value of the retardation Rth(550) in the thickness direction of the resin film, the more preferable. The absolute value of the retardation Rth(550) in the thickness direction of the resin film is preferably 20 nm or less, more preferably 15 nm or less, even more preferably 10 nm or less, and particularly preferably 5 nm or less. If the absolute value of the retardation Rth(550) in the thickness direction of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided. The absolute value of the retardation Rth(550) in the thickness direction is, for example, 0 nm or more.
[0042] The total light transmittance of the resin film is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the resin film is, for example, 99% or less. If the total light transmittance of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display properties can be provided. The total light transmittance of the resin film can be measured in accordance with JIS K 7361.
[0043] The haze of the resin film is preferably 10% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.5% or less. For example, the haze is 0.1% or more. If the haze of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display properties can be provided. The haze of the resin film can be measured according to JIS K 7361.
[0044] The tensile modulus of the resin film is preferably 1000 MPa to 3000 MPa, more preferably 1200 MPa to 2500 MPa, and further preferably 1500 MPa to 2000 MPa. If the tensile modulus of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The tensile modulus of the resin film can be measured at room temperature (23°C) in accordance with JIS K 7161.
[0045] The tensile breaking strength of the resin film is preferably 0.5 N to 20 N, more preferably 1 N to 15 N, and further preferably 3 N to 12 N. When the tensile modulus of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The tensile breaking strength of the resin film can be measured at room temperature (23°C) in accordance with JIS K 7161.
[0046] The breaking elongation of the resin film is preferably 1% to 10%, more preferably 2% to 8%, and further preferably 3% to 7%. If the breaking elongation of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The breaking elongation of the resin film can be measured by using a thermomechanical analyzer (TMA).
[0047] The moisture permeability of the resin film is preferably 20 g / m 2 / 24 hours~60g / m 2 / 24 hours, more preferably 25 g / m 2 / 24 hours~50g / m 2 / 24 hours, more preferably 30 g / m 2 / 24 hours~40g / m 2 / 24 hours. If the moisture permeability of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The moisture permeability of the resin film can be measured in accordance with JIS Z 0208 under conditions of a temperature of 40°C and a humidity of 92% RH.
[0048] E. Adhesive layer As described above, the resin film is preferably laminated to the first retardation film via the first adhesive layer, and is laminated to the second retardation film via the second adhesive layer. As described above, the adhesive layer is a pressure-sensitive adhesive layer or an adhesive layer. In one embodiment, the adhesive layer is preferably an adhesive layer. If the adhesive layer is an adhesive layer, the occurrence of dents can be further suppressed. The average refractive index n of the first adhesive layer AD1 and the average refractive index of the second adhesive layer, n AD2 The average refractive index of the first adhesive layer, n AD1 and the average refractive index of the second adhesive layer, n AD2 is the average refractive index of the resin film, n RF The difference between them can be adjusted to satisfy the above relationship.
[0049] E-1. Adhesive layer When the first adhesive layer and / or the second adhesive layer are pressure-sensitive adhesive layers, the first adhesive layer and the second adhesive layer may be formed of any suitable pressure-sensitive adhesive. Specific examples of pressure-sensitive adhesives include acrylic pressure-sensitive adhesives, rubber pressure-sensitive adhesives, silicone pressure-sensitive adhesives, polyester pressure-sensitive adhesives, urethane pressure-sensitive adhesives, epoxy pressure-sensitive adhesives, and polyether pressure-sensitive adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the pressure-sensitive adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., a pressure-sensitive adhesive having desired properties according to the purpose can be prepared. The base resin of the pressure-sensitive adhesive may be used alone or in combination of two or more types. From the viewpoints of transparency, processability, durability, etc., an acrylic pressure-sensitive adhesive (acrylic pressure-sensitive adhesive composition) is preferred.
[0050] The acrylic pressure-sensitive adhesive typically contains a (meth)acrylic polymer as a main component, and the (meth)acrylic polymer may be contained in the pressure-sensitive adhesive in an amount of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the pressure-sensitive adhesive.
[0051] The (meth)acrylic polymer contains alkyl (meth)acrylate as a main component as a monomer unit. Here, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in a proportion of preferably 80% by weight or more, more preferably 90% by weight or more, in the monomer components forming the (meth)acrylic polymer. Examples of the alkyl group of the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. The average carbon number of the alkyl group is preferably 3 to 9, more preferably 3 to 6.
[0052] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.
[0053] When the adhesive layer is a pressure-sensitive adhesive layer, the thickness of the pressure-sensitive adhesive layer may be set to any appropriate value. The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 10 μm, more preferably 2 μm to 8 μm, and even more preferably 3 μm to 7 μm. If the thickness of the pressure-sensitive adhesive layer is within the above range, the adhesion of each component member can be sufficiently ensured. As described above, in one embodiment, the thickness of the pressure-sensitive adhesive layer may be adjusted so that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
[0054] E-2.Adhesive layer When the first adhesive layer and / or the second adhesive layer is an adhesive layer, the adhesive layer can be formed of any suitable adhesive. For example, an active energy ray curable adhesive can be used. As the active energy ray curable adhesive, any suitable active energy ray curable adhesive can be used, for example, an ultraviolet ray curable adhesive, an electron beam curable adhesive can be used.
[0055] The active energy ray curable adhesive typically contains a monofunctional component, a polyfunctional component (curing component), and a photopolymerization initiator. The monofunctional component and the polyfunctional component are typically radical polymerizable compounds. Preferred monofunctional components include, for example, higher alkyl esters of (meth)acrylic acid and modified products thereof. Specific examples include isostearyl acrylate, lauryl acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and the like. Preferred polyfunctional components include, for example, monomers and / or oligomers having two or more functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples include polyethylene glycol diacrylate, trimethylpropane triacrylate, and glycerin triacrylate. Specific examples of monofunctional or polyfunctional components other than those mentioned above include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-methylol acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and 9-vinyl carbazole. In one embodiment, the monofunctional or polyfunctional component has a ring structure. Specific examples include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole. The monofunctional or polyfunctional components may each be used alone or in combination of two or more.
[0056] The active energy ray curable adhesive may further contain a cationic polymerizable compound as required. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of the monofunctional cationic polymerizable compound include p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane. Examples of the polyfunctional cationic polymerizable compound include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane. A silane coupling agent may be used as the cationic polymerizable compound. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane.
[0057] The active energy ray curable adhesive may further contain any suitable additive. For example, a plasticizer (e.g., an oligomer component), a crosslinking agent, a diluent, etc. may be mentioned. These additives are used in any suitable content depending on the purpose. In one embodiment, the active energy ray curable adhesive may further contain an organic compound having an aromatic ring. By using such a compound, the refractive index of the adhesive layer formed can be adjusted.
[0058] Details of the active energy ray-curable adhesive are described, for example, in JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.
[0059] The thickness of the adhesive layer is preferably 0.5 μm to 5 μm, more preferably 0.8 μm to 3 μm, and further preferably 1 μm to 2 μm. If the thickness of the adhesive layer is within the above range, the retardation layer and the resin film can be appropriately adhered to each other. As described above, in one embodiment, the thickness of the adhesive layer can be adjusted so that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
[0060] F. Image display device The retardation layer-attached polarizing plate described in the above items A to E can be applied to an image display device. Therefore, the embodiment of the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices). The image display device according to the embodiment of the present invention can include the retardation layer-attached polarizing plate on the viewing side. The retardation layer-attached polarizing plate can be laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). As described above, the retardation layer-attached polarizing plate of the embodiment of the present invention can suppress the occurrence of dents when it is attached to an image display panel. Therefore, the productivity of the image display device can be improved. EXAMPLES
[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.
[0062] (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C").
[0063] (2) Refractive index (2-1) Adhesive layer and resin film The adhesive layers formed in the examples and comparative examples, and the resin films used in the examples were measured using an Abbe refractometer (manufactured by ATAGO, product name "DR-M2 / 1550") at a wavelength of 589 nm and a temperature of 25°C. (2-2) Adhesive layer The adhesive used in the examples and comparative examples was applied to a cycloolefin polymer film (COP film) (thickness 100 μm), the same COP film was attached to the applied surface, and visible light was irradiated using an active energy ray irradiation device to obtain a cured layer (single film). The in-plane refractive index and the refractive index in the thickness direction of the obtained cured layer were measured using a prism coupler (manufactured by Cylon Technology, product name "SPA-4000"), and the average value of these was taken as the average refractive index of the adhesive layer. The measurement wavelength was 594 nm, and the measurement temperature was 23°C.
[0064] (3) Load-bearing compression evaluation The retardation layer-attached polarizing plate obtained in the examples and comparative examples was cut into a length of 1 cm and a width of 1 cm to prepare a sample. The second adhesive layer of the sample was attached to an aluminum reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%). Then, the sample was placed on a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness: 0.7 mm) so that the surface of the hard coat layer of the sample was in contact with the glass plate. Then, a weight was placed on a cone-shaped indenter (diameter 1.5 mm) from the aluminum reflector side via a polyethylene terephthalate (PET) sheet (manufactured by Toray Industries, Inc., thickness 80 μm) and pressed for 10 seconds. The weight (load) of the weight was changed to 300 g (1.7 MPa), 400 g (2.2 MPa), and 500 g (2.8 MPa), and measurements were performed. After that, the weight and the indenter were removed, and the surface of the retardation layer-attached polarizing plate that had been in contact with the glass plate was visually observed in reflection at a polar angle of 30° to 60° and around one azimuth angle to confirm the presence or absence of dents, and the maximum load at which no dents were observed was defined as the load capacity. In addition, when the surface of the retardation layer-attached polarizing plate is defined as the X-axis and the Y-axis, and the axis perpendicular to the XY plane is defined as the Z-axis, the angle inclined from the Z-axis to the XY plane direction was defined as the polar angle (θ), and the MD direction of the polarizing plate used in the retardation layer-attached polarizing plate was defined as 0°, and the measurement angle defined between the MD direction of this polarizing plate and the counterclockwise direction was defined as the azimuth angle (φ).
[0065] (4) Interference unevenness The retardation layer-attached polarizing plate obtained in the examples and comparative examples was attached to a V3 reflector (manufactured by NEODIS) via the outermost adhesive layer. Next, an acrylic adhesive was applied to the polarizing plate side of the retardation layer-attached polarizing plate to form an adhesive layer with a thickness of 100 μm, and then a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness: 0.7 mm) was attached via the adhesive layer. After that, the reflection was observed visually under a fluorescent lamp (three-wavelength tube), and the evaluation was performed according to the following criteria. The observation was performed for polar angles of 20° to 60° and for an azimuth angle of one revolution. Note that unevenness visible even under sunlight was not included in the interference unevenness. ○ (Good): No visible streaks or irregular irregularities in pink, green or black caused by interference light. △ (Fair): Irregular unevenness due to interference light visible in pink, green, and black is visible, but no streaky unevenness is visible. × (room for improvement): Stripes of unevenness caused by interference light that appears pink, green, and black are visible.
[0066] (5) Reflective hue (polar angle 45° hue) The polarizing plates with retardation layers obtained in the examples and comparative examples were cut into a length of 1 cm and a width of 1 cm to prepare samples. The second adhesive layer of the sample was attached to an aluminum reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%). When observing the sample in reflection at a polar angle of 45° around one azimuth angle, the sample with a change in color was rated as 1, and the sample without a change in color was rated as 2. Observation was also performed at a polar angle of 0°, and the sample with a color that matched the color around one azimuth angle was rated as 3 for evaluation.
[0067] (6) Judgment The suitability of the retardation layer-attached polarizing plate for use in an image display device was evaluated according to the following criteria. 〇〇 (best): Load-bearing test is 2.6Mpa or more, interference unevenness is 〇 (good), and reflection hue is 3 ○ (Good): The load-bearing test is 2.0 MPa or more, interference unevenness is ○ (good), and the reflection hue is 2 or 3. △ (Fair): The load-bearing test is 2.0 MPa or more, interference unevenness is △ (Fair) or ○ (Good), and reflection hue is 1, 2, or 3. × (room for improvement): The load resistance test is less than 2.0 MPa, the interference unevenness is × (room for improvement), or the reflection hue is 1
[0068] [Production Example 1] Preparation of adhesive composition 1. Preparation of Base Polymer A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the nitrogen. The liquid temperature in the flask was kept at around 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to obtain a solution of a (meth)acrylic polymer with a weight average molecular weight of 2 million, adjusted to a solid content concentration of 30%.
[0069] 2. Preparation of acrylic adhesive composition An acrylic adhesive composition was prepared by blending 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, product name "Coronate L") and 0.1 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.
[0070] [Production Example 2] Preparation of Adhesive 1 50 parts by weight of a caprolactone derivative (manufactured by Daicel Corporation, trade name "Placcel FA1DDM"), 40 parts by weight of acryloylmorpholine (ACMO: registered trademark, manufactured by Kohjinsha), 10 parts by weight of an acrylic polymer (manufactured by Toagosei Co., Ltd., trade name "ARFON UP-1190"), 3 parts by weight of a photopolymerization initiator 1 (manufactured by Nippon Kayaku Co., Ltd., trade name "KAYACURE DETX-S"), and 3 parts by weight of a photopolymerization initiator 2 (manufactured by BASF Japan Ltd., trade name "IRGACURE907") were mixed to prepare adhesive 1. The obtained adhesive 1 was photocured (300 mJ / cm2 ) The average refractive index of the cured product obtained was 1.51.
[0071] [Production Example 3] Preparation of Adhesive 2 60 parts by weight of fluorene-based acrylate (Osaka Gas Chemicals, product name "Oxol EA-F5710"), caprolactone derivative (Daicel, product name "Placcel FA1DDM"), 20 parts by weight of acryloylmorpholine (KJ Chemicals, product name "ACMO"), 5 parts by weight of ARFON UP-1190 (Toagosei), 1 part by weight of photopolymerization initiator 1 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, IGM Resins BV, product name "Omnirad 819"), 2 parts by weight of photopolymerization initiator 2 (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad 184", IGM Resins BV), and 2 parts by weight of diethylthioxanthone (Nippon Kayaku, product name "KAYACURE DETX-S") were stirred at 50°C for 1 hour to prepare adhesive 2. The obtained adhesive 2 was photocured (300 mJ / cm 2 ) The average refractive index of the cured product obtained was 1.57.
[0072] [Example 1] <Preparation of polarizing plate> 1. Preparation of Polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of 6 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0073] 2. Preparation of Polarizing Plates An HC-COP film was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curing adhesive. The HC-COP film was a film in which an HC layer (4 μm thick) was formed on a cycloolefin resin (COP) film (25 μm thick), and the COP film was attached to the polarizer side. The COP film had a Re (550) of 135 nm. Next, the resin substrate was peeled off, and a triacetyl cellulose (TAC) film (20 μm thick) was attached to the peeled surface via an ultraviolet-curing adhesive. In this way, a polarizing plate having a configuration of HC layer / COP film (protective layer) / polarizer / TAC film (protective layer) was obtained.
[0074] 3. Preparation of polarizing plate with retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a PET film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90° C. for 2 minutes. The liquid crystal layer thus formed was then irradiated with 100 mJ / cm 2 using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal layer with light of 1000 nm to form a first retardation layer, which is a liquid crystal alignment solidified layer, on the PET film. The thickness of the first retardation layer was 2 μm, and the in-plane retardation Re(550) was 270 nm. Furthermore, the first retardation layer had a refractive index distribution of nx>ny=nz. The adhesive obtained in Production Example 2 was applied to the TAC film side surface of the polarizing plate obtained above, and the first retardation layer obtained above was attached via an adhesive layer having a thickness of 1 μm. Then, the PET film was peeled off from the first retardation layer. Separately, a second retardation layer was formed on a PET film in the same manner as above, except that the coating thickness was changed and the orientation treatment direction was set to a 75° direction relative to the absorption axis direction of the polarizer when viewed from the viewing side. The thickness of the second retardation layer was 1 μm, and the in-plane retardation Re (550) was 140 nm. Furthermore, the second retardation layer had a refractive index distribution of nx>ny=nz. The adhesive obtained in Production Example 1 was applied to the PET film peeling surface of the first retardation layer to form an adhesive layer (first adhesive layer) having a thickness of 5 μm, and a TAC film (Konica Minolta, thickness 20 μm, average refractive index 1.49) was attached. Similarly, the adhesive obtained in Production Example 1 was applied to the surface of the TAC film not in contact with the first retardation layer to form an adhesive layer (second adhesive layer) having a thickness of 5 μm, and the surface of the second retardation layer obtained above on which the PET film was not laminated was attached. Next, the PET film was peeled from the second retardation layer, and the adhesive obtained in Production Example 1 was applied to the peeling surface to form an adhesive layer having a thickness of 25 μm, and a retardation layer-attached polarizing plate was obtained. Note that, until the evaluation, a polyethylene terephthalate film (PET film, separator) having a thickness of 38 μm treated with a silicone-based release agent was attached to the second adhesive layer. The results are shown in Table 1.
[0075] [Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the first adhesive layer and the second adhesive layer were 1 μm thick adhesive layers formed using the adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0076] [Example 3] A polarizing plate with a retardation layer was obtained in the same manner as in Example 2, except that a cyclic olefin resin film (manufactured by Zeon Corporation, product name "ZEONORFILM ZF14", thickness 13 μm, average refractive index 1.52) was used instead of the TAC film as the resin film. The results are shown in Table 1.
[0077] [Example 4] A polarizing plate with a retardation layer was obtained in the same manner as in Example 3, except that adhesive 2 obtained in Production Example 3 was used instead of adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0078] [Example 5] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a cyclic olefin resin film (manufactured by Zeon Corporation, product name "ZEONORFILM ZF14", thickness 13 μm, average refractive index 1.52) was used instead of the TAC film as the resin film. The results are shown in Table 1.
[0079] Comparative Example 1 A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a resin film was not laminated, and the first retardation layer and the second retardation layer were laminated via a pressure-sensitive adhesive layer (thickness: 15 μm) formed using the pressure-sensitive adhesive obtained in Production Example 1. The results are shown in Table 1.
[0080] Comparative Example 2 A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that in the preparation of the polarizing plate, a TAC film was not attached to the polarizer, a resin film was not laminated, and the first retardation layer and the second retardation layer were laminated via an adhesive layer (thickness 1 μm) formed using the adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0081] [Table 1]
[0082] [evaluation] As is clear from Table 1, the retardation layer-attached polarizing plates of the examples of the present invention were able to suppress the occurrence of interference unevenness and dents. [Industrial Applicability]
[0083] The retardation layer-attached polarizing plate according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices. [Explanation of symbols]
[0084] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 22 First adhesive layer (adhesive layer) 23 Second adhesive layer (adhesive layer) 31 First retardation layer 32 Second retardation layer 41 First adhesive layer (adhesive layer) 42 Second adhesive layer (adhesive layer) 50 Resin Film 60 Adhesive layer 100 Polarizing plate with retardation layer
Claims
1. The present invention has, in this order, a polarizing plate including a polarizer; a first retardation layer which is a layer in which a liquid crystal compound is aligned and fixed; a resin film; and a second retardation layer which is a layer in which a liquid crystal compound is aligned and fixed. a slow axis of the first retardation layer intersects with a slow axis of the second retardation layer; a slow axis of the first retardation layer intersects with an absorption axis of the polarizer, The resin film has a thickness of 10 μm to 30 μm.
2. the resin film is laminated to the first retardation layer via a first adhesive layer, The average refractive index of the first adhesive layer, n AD1 and the average refractive index n of the resin film RF and satisfy the following relationship: -0.03<n AD1 ―n RF <0.05
3. the resin film is laminated to the second retardation layer via a second adhesive layer, The average refractive index of the second adhesive layer, n AD2 and the average refractive index n of the resin film RF and satisfy the following relationship: -0.03<n AD2 ―n RF <0.05
4. the resin film is laminated to the first retardation layer via a first adhesive layer, the resin film is laminated to the second retardation layer via a second adhesive layer, 2. The polarizing plate with a retardation layer according to claim 1, wherein the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
5. 2. The retardation layer-attached polarizing plate according to claim 1, wherein the resin film is a cyclic olefin-based resin film or a cellulose-based resin film.
6. 2. The polarizing plate with a retardation layer according to claim 1, wherein the resin film has a refractive index distribution of nx=ny>nz.
7. The first retardation layer has an Re(550) of 200 nm to 300 nm, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°, The retardation layer-attached polarizing plate according to claim 1, wherein the second retardation layer has an Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°.
8. The retardation layer-attached polarizing plate according to claim 2 , wherein the adhesive layer is an adhesive layer.
9. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .
10. 10. The image display device according to claim 9, which is an organic electroluminescence display device.
11. An image display device comprising the retardation layer-attached polarizing plate according to claim 8 .
12. 12. The image display device according to claim 11, which is an organic electroluminescence display device.
Citation Information
Patent Citations
Control device for vehicular headlight, control method for vehicular headlight, and vehicular headlight system
JP2022014611A